Downscaling SDG6 (clean water and sanitation) to decision relevant scales - Cai, Ximing; Celeste, Alcigeimes B.; Du, Erhu; Foster, Timothy; Mohtar, Rabi H.; Ringler, Claudia; Sabri, Dahlia; Satur, Paul; Singh, Riddhi; Stephan, Raya M. (Informa UK Limited, 2025)
Current efforts to localize Sustainable Development Goals (SDGs) are hindered by uncertainties and risk, insufficient monitoring and inappropriate indexes, and limited exchanges among countries/regions. We provide perspectives on downscaling SDG6 – clean water and sanitation – to decision relevant scales everywhere in the world. We synthesize existing experiences to identify promising approaches; test entry points and applicability of SDG indicators in pilot basins, cities and countries; and promote evidence based indexes and dashboards for local water management. In this way, we directly respond to a key question of the UN 2023 SDG progress report on how progress towards SDG6 can be accelerated.